2006
DOI: 10.1080/08035250500447936
|View full text |Cite
|
Sign up to set email alerts
|

Infant feeding and cost of health care: A cohort study

Abstract: Lack of breastfeeding and higher use and cost of health care are significantly associated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 19 publications
1
29
0
2
Order By: Relevance
“…In Cattaneo et al's (2006) study, infants who were exclusively breast fed until 3 months of age had lower healthcare costs per infant per year for ambulatory care and hospital care. Ball and Wright (1999) and Smith et al (2002), and many other studies, found that lack of breast feeding was significantly associated with higher usage and cost of healthcare services (Ball and Wright, 1999;Smith et al, 2002;Kramer et al, 2003;Abolyan, 2006;Ramani and Ambalavanan, 2013).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…In Cattaneo et al's (2006) study, infants who were exclusively breast fed until 3 months of age had lower healthcare costs per infant per year for ambulatory care and hospital care. Ball and Wright (1999) and Smith et al (2002), and many other studies, found that lack of breast feeding was significantly associated with higher usage and cost of healthcare services (Ball and Wright, 1999;Smith et al, 2002;Kramer et al, 2003;Abolyan, 2006;Ramani and Ambalavanan, 2013).…”
Section: Resultsmentioning
confidence: 83%
“…The World Health Organization (WHO) endorses breast feeding as the most efficient nutritional practice for the health and well-being of preterm infants (WHO/UNICEF, 1990, 1992. Indeed, breast feeding reduces hospitalisation costs by providing active protection for LBW infants against a number of serious morbidities (Rogowski, 1998;Ball and Wright, 1999;Smith et al, 2002;Cattaneo et al, 2006). The recommendation to feed LBW infants predominantly with their mother's milk from the first hour of life, followed by breast feeding, is supported by most research.…”
Section: Introductionmentioning
confidence: 99%
“…However, exclusive lactation during the first 6 months of a child's life, has the potential to reduce out-of-pocket household expenditures on healthcare (Cattaneo et al, 2006), which is important given that 24% of household in Ecuador live below the poverty line (Bertoli & Marchetta, 2014;INEC-DIPES, 2010). It was reported that in the United Stated exclusive lactation can save up to $1000 USD per family per year due to the savings accrued by not buying artificial infant formula (Schanler, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Breastfeeding also has health benefits for the mother [5], including a reduced risk of breast and ovarian cancer compared to women who do not breastfeed [3]. Breastfeeding is cost saving for the family and the community [6,7]. …”
Section: Introductionmentioning
confidence: 99%